(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper presents a numerical study on the influence of tether geometry on the performance of the MoorPower wave energy system, developed for integration with offshore aquaculture infrastructure. The MoorPower concept enables energy harvesting from the motion of a moored barge through a belt-based power take-off (PTO) system, offering a pathway to reduce diesel dependency in remote marine operations. A coupled time-domain model, using WEC-Sim and MoorDyn with hydrodynamic inputs from Nemoh, was used to simulate the system’s dynamic response. The effect of varying tether inclination and azimuth angles on annual average power (AAP) was systematically assessed for a barge located off the southeast coast of Tasmania. Results indicate that tether inclination has a dominant effect on power output, with optimal performance achieved when tethers are angled inward at 10°. This configuration aligns with the elliptical trajectory of the PTO attachment points driven by the barge’s six-degree-of-freedom motion. The results demonstrate promising power levels—sufficient to offset at least 50% of the diesel consumption of a standard commercial fish-feeding barge. These findings offer valuable design guidance for maximizing energy yield while maintaining operational compatibility with aquaculture activities.